HOUSEHOLD LEVEL ANALYSIS OF FOOD INSECURITY AND COPING STRATEGIES: EVIDENCE FROM ENUGU STATE, NIGERIA. - onunka, cynthia nneka (Advances in Social Sciences Research Journal, 2018)
The study analysed the strategies used by the rural households to cope with food insecurity in Udi local government area of Enugu state. Data were collected through household surveys using semi-structured questionnaires. Descriptive and inferential statistical tools were employed to analyse the data for the study. Households were grouped based on their food security status (food secure and food insecure). The study result showed that the two-group household differed significantly in some of their socio-economic characteristics. The study confirms that the coping strategies employed by the vulnerable households were not mutually exclusive, rather a mixed approach comprising multiple strategies were adopted to cushion food insecurity shocks. Furthermore, socioeconomic factors such as income (p<0.01), marital status (p<0.1) and educational level (p<0.01) were found to negatively influence the number of coping strategy adopted by rural households while the dependency ratio (p<0.01) was positively significant. Policy implications were drawn for education promotion, poverty alleviation programs and the creation of sustainable off-farm employment opportunities.